Research of Influence of Bearing Preload on Dynamic Characteristic of High-speed Heavy-load Planetary Gear Transmission - Xiangyang Xu; Song Fu; Xun Han; Xing Ai (Jixie chuandong)
In order to analyze the influence of bearing preload on the dynamic characteristics of high-speed and heavy-load planetary gear transmission system， a dynamics model of high-speed heavy-load planetary gear transmission is established. Considered bearing preload factors， the preload of planetary pin bearing influence is analyzed for system support stiffness， natural frequency， internal and external Engagement vice dynamic meshing force. The results show that the planetary pin bearing preload can effectively increase the support stiffness of the planetary pin； the natural frequency of the system decreases with the preload and then increases， and increases with the increase of the clearance；the peak value of the dynamic meshing force of the internal and external meshing pairs of the planetary gear increases with the preload and then decreases， and increases with the increase of the clearance. The research results can provide support for optimizing the bearing preload of high-speed and heavy-load planetary gear transmission.